Preparation and characterization of polyvinyl alcohol/starch blend film composite - Ngadi, Norzita (Trans Tech Publications, 2014)
Nowadays, the demands of plastics materials are increasing rapidly. Nevertheless, most of these products are non-environmentally friendly and non–biodegradable. Polyvinyl alcohol (PVA) is one of the polymers that have been investigated widely for the potential for use as biodegradable plastics. However, the applications of PVA materials are limited due to their high cost and slow degradation process especially under anaerobic condition. Therefore, this study was conducted to investigate the effect of varying the PVA and starch content on the composite properties. A series of blend films with different ratio of PVA and starch were prepared by solution casting method. The results of this study have revealed that the polyvinyl alcohol and starch at a weight ratio of 70:30 was selected as the best blending composition, whereby the 70:30 blend film have the best elongation at break at about 334.69%, with a tolerable tensile strength value and water absorption capacity of 3.830 MPa and 49.59%, respectively.